2021
DOI: 10.7759/cureus.14146
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Inflammatory Demyelinating Polyradiculoneuropathy During the COVID-19 Pandemic: Telemedicine Limitations and Strategies for Improvement

Abstract: Chronic Inflammatory Demyelinating Polyneuropathy (CIDP) is a relapsing-remitting or progressive inflammatory neuropathy, which can present in a multitude of phenotypes. It can be a challenging condition to diagnose and requires thorough clinical evaluation and electrodiagnostic testing. With the outbreak of coronavirus disease in 2019 (COVID-19), large portions of the medical field converted to telemedicine to facilitate patient visits. We report a case of a 50-year-old female who was seen via video visit dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Initially, concerns were raised that covid-19 or vaccination would worsen disease or precipitate relapse in patients with pre-existing inflammatory central nervous system and neuromuscular disease 157. Some evidence suggested that more substantial harms resulted from difficult and delayed diagnosis of general neurological disorders, anxiety of the unknown for patients, and reduced disease control resulting from fewer healthcare interactions and alterations in treatment strategies in the first year of covid-19, than resulted from relapses precipitated by infection or vaccination 157158…”
Section: Effect On Pre-existing Inflammatory Neurological Disease (Ce...mentioning
confidence: 99%
“…Initially, concerns were raised that covid-19 or vaccination would worsen disease or precipitate relapse in patients with pre-existing inflammatory central nervous system and neuromuscular disease 157. Some evidence suggested that more substantial harms resulted from difficult and delayed diagnosis of general neurological disorders, anxiety of the unknown for patients, and reduced disease control resulting from fewer healthcare interactions and alterations in treatment strategies in the first year of covid-19, than resulted from relapses precipitated by infection or vaccination 157158…”
Section: Effect On Pre-existing Inflammatory Neurological Disease (Ce...mentioning
confidence: 99%